Soybean oil supplementation for cattle: effects on in vitro digestion, dairy cattle performance, and milk fat composition - Rodrigues, João Paulo Pacheco (2017)
The present work was a compilation of three studies evaluating soybean oil (SBO) as fat supplement for dairy cows. The first study aimed to to evaluate the effects of SBO supplementation with different forages on in vitro gas production kinetics, methane (CH 4 ) emissions and potentially digestible neutral detergent fibre (pdNDF) digestibility (IVpdNDFD). Samples of whole-crop maize silage (MS), sugarcane (SC), ryegrass (RG), brachiaria grass (BG) and guinea grass (GG) were incubated for 72h with three concentrations of SBO (0, 30 and 60 g/kg of dry matter (DM)) in a fully automated in vitro gas system. Three runs were conducted using buffered rumen fluid from three cows. The SBO increase affected acetate proportion in VFA, acetate to propionate ratio, and total gas production at 72h differently according to the forage. Soybean oil inclusion did not affect total gas production for RG and BG; however, decreased quadratically for MS and SC and increased quadratically for BG. The SBO quadratically decreased CH 4 emission both as mL/g of OM and % of total gas production. The IVpdNDFD decreased 21.2 and 12.9% when SBO level was increased for MS and SC, respectively, without showing any effects for GG, BG and RG. In conclusion MS and SC are more sensitive to adverse effects of SBO addition from 30 to 60 g kg -1 MS on rumen digestion of pdNDF than RG, GG and BG. The second study aimed to quantify the productive and metabolic responses, and digestive changes in dairy cows fed various concentrations of SBO in high concentrate, sugarcane-based diets. Eight rumen-cannulated multiparous Holstein cows (body weight (BW) = 574 ± 19.1 kg and 122 ± 6.9 days in milk), averaging 22.5 ± 1.22 kg/d of milk were assigned to replicated 4 × 4 Latin squares. The experimental period lasted 21 d as follows: 14 d for adaptation, followed by a sampling period from d 15 to 21. The diets were formulated with increasing concentrations of SBO (% of DM): control (0%), low (LSBO; 1.57%), medium (MSBO; 4.43%) and high (HSBO; 7.34%). Dry matter intake (DMI) decreased quadratically in response to SBO addition. The greatest decrease in DMI was observed in MSBO and HSBO diets. Both milk and energy corrected milk (ECM) yield were quadratically affected by the SBO inclusion, with a slight decrease up to MSBO and substantial decrease in the HSBO diet. The milk fat concentration linearly decreased from 3.78% in the control to 3.50% in the HSBO diet. The potentially digestible neutral detergent fiber digestibility in the rumen decreased from vii55.7% in the control to 35.2% in the HSBO diet. The fractional rate of digestion of potentially digestible neutral detergent fiber in the rumen decreased linearly from 3.13 to 1.39%/h from the control to HSBO diet. The fractional rate of indigestible neutral detergent fiber passage in the rumen was quadratically affected, with the lowest value (2.25%/h) for the HSBO diet. Rumen pH increased from 6.42 to 6.67, and ammonia nitrogen decreased from 28.1 to 21.4 mg/dL, in the control and HSBO diets, respectively. Rumen volatile fatty acids decreased quadratically, with the greatest decrease observed in MSBO and HSBO diets. Serum concentrations of glucose, non-esterified fatty acids and beta-hydroxybutyrate were unaffected by SBO inclusion. However, serum concentrations of total cholesterol and high-density and low-density lipoproteins linearly increased with increasing concentrations of SBO in the diet. Soybean oil supplementation at 1.57% of the diet DM proved to be a safe concentration for dairy cows fed high concentrate diets with sugarcane as the sole forage. Inclusion of SBO at concentrations from 4.43 to 7.34% of the diet DM decreased DMI, ECM production, fiber digestibility and rumen fermentation being not recommended. The third study aimed to investigate the effects of increasing concentrations of SBO in sugarcane-based diets on omasal digesta and milk fatty acids (FA) profile, focusing on conjugated linoleic acid (CLA) in milk. The diets were the same reported for the second study (control, LSBO, MSBO and HSBO) Experiment 1 (EXPI) was designed to quantify the flow of FA to the omasum and milk FA profile. In EXPI, eight rumen-cannulated multiparous Holstein cows averaging 574 ± 19·1 kg BW and 122 ± 6·9 days in milk were used in a replicated 4 × 4 Latin square design. Experiment 2 (EXPII) was designed to quantify the milk FA profile in cows after calving. In EXPII 14 primiparous (545 ± 17·2 kg BW) and eight multiparous (629 ± 26·7 kg BW) Holstein cows were used after calving. The concentration of 11trans-18:1, 9cis,11trans-18:2 CLA, and 9cis,11trans-18:2 CLA in omasal digesta increased linearly with the addition of SBO. Soybean oil increased quadratically the biohydrogenation rate of polyunsaturated FA (PUFA), with a slightly increase from MSBO to HSBO. Milk fat concentration in both experiments decreased with SBO supply; however, fat yield was not affected in EXPII. In both experiments, the concentration (g/kg) of 9cis,11trans-18:2 CLA in milk increased linearly in despite of the yield (g/d) increased quadratically. 10trans,12cis-18:2 CLA in milk was detected in MSBO and HSBO diets. The addition of SBO proved to be a feasible alternative to increase the rumen outflow of 11trans-18:1 and milk 9cis,11trans-18:2 CLA concentration; however, SBO supplementation greater than 15.7 g SBO/kg DM decreases milk and fat yield without additive response on 9cis,11trans-18:2 CLA yield.